Analisis Pengaruh Debt to Equity Ratio (DER) Current Ratio (CR) dan Return on Asset (ROA) Terhadap Harga Saham PT Ultrajaya Milk Industry & Trading Company Tbk Periode 2019-2023 - Rahel, Rahel Purba (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2025)
The purpose of this study was to analyze the effect of debt-equity ratio (DER), current ratio (CR), and return on assets (ROA) on the share price of PT Ultrajaya Milk Industry & Trading Company Tbk during 2019-2023. This research method is quantitative using secondary data obtained from the company's financial statements. The results of this study indicate that DER, CR, and ROA partially have an insignificant effect on the company's stock price. The coefficient of determination (R²) value of 38.8% indicates that the variation in stock prices is only partially explained by the DER, CR, and ROA variables, and the remaining 61.2% is influenced by other factors outside the research model. The study concludes that although financial ratios such as DER, CR, and ROA are important, other factors such as market conditions and economic sentiment may have a greater impact on the movement of a company's stock price.